Wideband Low Loss Bending-Resistance Hollow-Core Fiber With Hybrid Claddings of Antiresonance and Photonic Bandgap Guidance Mechanisms - Yundong Hao; Huiyi Guo; Yong You; Zhi Wang; Yan-Ge Liu (IEEE Photonics Journal, 2023)
Hollow-core anti-resonant fibers (HC-ANF) have the advantages of low scattering loss, wide bandwidth and simplicity of preparation, but are sensitive to bend, which limits their practical applications. On the contrary, hollow-core photonic bandgap (HC-PBGF) fibers have lower confinement loss and more robust bending characteristic, but exhibit unavoidable high scattering loss, influence of surface modes and stricter manufacturing processes. In this article, a novel hollow-core hybrid cladding fiber (HC-HBCF) which consists of anti-resonant circular tubes of inner cladding and periodically arranged air holes of outer cladding is proposed and investigated numerically. The results show that combining the claddings of antiresonance and photonic bandgap guidance mechanisms can effectively reduce the mode confinement loss by five and six orders of magnitude compared to the fibers with two claddings alone respectively. The proposed HC-HBCF exhibits similar excellent low scattering loss and spectral flatness as the single-tube anti-resonant fiber. Specifically, the proposed HC-HBCF exhibits the confinement loss of 5 × 10−5 dB/km at 1550 nm and a total loss of 0.1 dB/km from 1430 nm to 1770 nm. Meanwhile, the hybrid cladding fiber has an outstanding bending property with a bending loss of 0.16 dB/km at a small bending radius of 2 cm. The mode properties of HC-HBCF are also calculated and analyzed, indicating that the hybrid cladding fiber has a unique potential in controlling modal content.